Correlation of docetaxel administration duration, dosage, and patient age with epiphora severity: a retrospective observational study in breast cancer patients - Erna, Riani; Mintardi, Dita; Qodir, Nur; Bahar, Erial (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Epiphora, or excessive tearing, is a frequent yet under-recognised adverse effect of docetaxel, a taxane-based chemotherapeutic agent used in breast cancer treatment. Inflammatory and fibrotic changes within the lacrimal drainage system are hypothesised as the primary mechanisms. This study aimed to evaluate the correlation between docetaxel administration duration and epiphora severity, alongside the impact of cumulative dosage and patient age. A retrospective observational study was conducted at Mohammad Hoesin Hospital Palembang, involving 25 breast cancer patients who reported epiphora during docetaxel chemotherapy. Patients with pre-existing ocular conditions, prior lacrimal surgery, or concurrent use of epiphora-inducing medications were excluded. Epiphora severity was assessed using the Munk score, and statistical analyses included Pearson’s correlation and multiple regression. Findings demonstrated a strong positive correlation between epiphora severity and docetaxel duration (r = 0.645, p < 0.05), cumulative dosage (r = 0.618, p < 0.05), and patient age (r = 0.703, p < 0.05). Limitations include the retrospective design, small sample size, and subjective assessment tools. These results emphasise the importance of monitoring for epiphora during docetaxel therapy, with early ophthalmologic intervention recommended. Further prospective studies are needed to clarify pathophysiological mechanisms and optimise management strategies for chemotherapy-induced epiphora.